Ionizing Radiation and Cancer Risks: What Have We Learned From Epidemiology? - Gilbert, Ethel S. (2009)
PURPOSE: Epidemiologic studies of persons exposed to ionizing radiation offer a wealth of information on cancer risks in humans. The Life Span Study cohort of Japanese A-bomb survivors, a large cohort that includes all ages and both sexes with a wide range of well-characterized doses, is the primary resource for estimating carcinogenic risks from low linear energy transfer external exposure. Extensive data on persons exposed for therapeutic or diagnostic medical reasons offer the opportunity to study fractionated exposure, risks at high therapeutic doses, and risks of site-specific cancers in non-Japanese populations. Studies of persons exposed for occupational and environmental reasons allow a direct evaluation of exposure at low doses and dose rates, and also provide information on different types of radiation such as radon and iodine-131. This article summarizes the findings from these studies with emphasis on studies with well-characterized doses. CONCLUSIONS: Epidemiologic studies provide the necessary data for quantifying cancer risks as a function of dose and for setting radiation protection standards. Leukemia and most solid cancers have been linked with radiation. Most solid cancer data are reasonably well described by linear-dose response functions although there may be a downturn in risks at very high doses. Persons exposed early in life have especially high relative risks for many cancers, and radiation-related risk of solid cancers appears to persist throughout life.